Prestasi sebagai Mediator Achievement Goal Orientation dan Subjective Well-Being Mahasiswa - Sandjaja, Meilani (Universitas Muhammadiyah Metro, 2023)
Entering higher education gives students new roles and responsibilities. Accompanied by increasing tasks, burdens, and obligations they possess, this causes students to face various issues. The various challenges faced by students influence their subjective well-being (SWB). This study aims to examine GPA as a mediating variable between achievement goal orientation (AGO) and subjective well-being (SWB), an area that hasn't been extensively researched. The participants of this study amounted to 175 individuals, active students from various departments, aged between 18-22 years old. Data was collected using the SWB scale, AGO scale, and GPA to measure students' academic achievements, distributed through online surveys. The research findings indicate that GPA does not significantly mediate between AGO and SWB. This study also discovered that AGO has a positive and significant relationship with SWB and GPA.